Effectiveness of Chlorine Against Tulane Virus, A Human Norovirus Surrogate, and Escherichia coli in Preharvest Agricultural Water - Ashlyn Lake; Nuradeen Garba Yusuf; Mya Maybank; Sarah Johnson; Christopher K. Mutch; Alexander P. Mueck; Simon S. Riley; Arie H. Havelaar; Naim Montazeri (Journal of Food Protection)
The use of fecally polluted water increases the risk of crop contamination with human norovirus (HuNoV) and its transmission to humans, particularly through ready-to-eat foods such as fresh produce. Preventing such exposure at preharvest stages is critical to ensure food safety throughout the supply chain. Despite HuNoV being the leading cause of foodborne illnesses in the United States, effective mitigating strategies in preharvest agricultural water remain underdeveloped. This research evaluated the effectiveness of calcium hypochlorite, a commercially available sanitizer to inactivate the Tulane virus, a surrogate for HuNoV, and Escherichia coli TVS 353 in preharvest agricultural waters. Water samples from two Florida farms were collected and inoculated with each microbial type, then treated with different free chlorine dosages (2, 4, 10, 15, 20, 30, and 40 ppm) for 5 and 10 min. The treatments were conducted at 12 °C to reflect colder months in Florida, aligning with the temperature specification outlined in the EPA/FDA protocol. Microbial counts were performed using plaque assay for Tulane virus and plate counts for E. coli. Since increasing the contact time from 5 to 10 min did not significantly enhance microbial inactivation rates (p > 0.05), kinetic models were fit to inactivation data for the 5-min contact time. The log10-logistic model predicted that achieving the EPA/FDA 3-log10 microbial reduction criteria in the agricultural water samples required treatment with free chlorine ranging between 0.6 and 0.9 ppm for E. coli and 9.6–23 ppm for Tulane virus. Compared to E. coli, Tulane virus was more resistant to inactivation with higher variability in reduction rates between the two agricultural water samples (p < 0.001). The necessity for elevated doses needed to inactivate viruses demands additional investigation, emphasizing the importance of implementing risk-based, environmentally safe treatments for agricultural water.